Analisis Pengaruh Demografi dan Kepribadian dalam Penentuan Instrumen Investasi di Yogyakarta - , Dias Setianingsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Development of investment in Indonesia at this time, began to pay special attention to the economists, because its presence has a very important role in supporting the economy of a country. Financial behavior plays an important role in a person's decision to invest. In addition, investment choices are also based on lifestyle and demographic characteristics. The purpose of this study was to analyze and determine the extent of demographic and personality variables significantly affect investors in the determination of investment instruments in the Yogyakarta area. The primary data about the respondents and their level of risk priorities of respondents that are useful for the determination of investment instrument. This study uses a type of causal research that emphasizes the extent to which these variables are related. Data collection techniques can be used is the collection of survey data. To answer the problem and test the hypothesis proposed in this research used descriptive analysis and Kruskal Wallis and Mann Whitney test. From the results of hypothesis testing can be concluded that there are significant differences the influence of demographic factors with the type of investments and investor behaviour in dealing with investment risk.